2013
DOI: 10.1111/j.1751-1097.2012.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Vaccinia Virus by Natural Sunlight and by Artificial UVB Radiation

Abstract: This study determined the sensitivity of vaccinia virus, an orthopox virus commonly used as a surrogate for variola virus (etiological agent of smallpox), exposed to UVB radiation emitted by a solar simulator, or to direct natural sunlight. The data obtained indicate that: (1) the virucidal effect of natural sunlight can be mimicked adequately by an artificial light source with similar spectral characteristics in the UVB, (2) viral sensitivity to UVB or to solar radiation can be correlated with experimental da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…the survival levels for 1 − log 10 or 2 − log 10 are 10% and 1%, respectively . Microbial survival can thus be estimated by combining the microbial sensitivities that have been measured or estimated previously (, reviewed in ) with the atmospheric radiances calculated by the method described here for aerosols suspended at different altitudes under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…the survival levels for 1 − log 10 or 2 − log 10 are 10% and 1%, respectively . Microbial survival can thus be estimated by combining the microbial sensitivities that have been measured or estimated previously (, reviewed in ) with the atmospheric radiances calculated by the method described here for aerosols suspended at different altitudes under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In river systems, constant fluence is unlikely, because microorganisms move within the water column and sunlight intensity changes with respect to time of day and ambient meteorological conditions. Moreover, as most UV‐B is delivered during a 4‐hour period (2 h either side of solar noon) a constant fluence cannot be assumed .…”
Section: Resultsmentioning
confidence: 99%
“…A previously proposed model suggested that approximately 41 times the fluence of UV‐C would be required to inactivate viruses by the same magnitude when using UV‐B ; for the Vaccina virus, 33 times more UV‐B was required than UV‐C to achieve the same level of inactivation by the same authors . This factor has been used in biodefense calculations and influenza epidemic risk assessments .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The setup used to expose P.aeruginosa to direct sunlight was similar to that previously described for exposing virulent B. pseudomallei and vaccinia virus . A 100 μl aliquot of the bacterial stock washed twice in sterile distilled water was dispensed in the middle of an UV‐transparent petri dish (Lumox UV‐permaeable 50TC, sterile; Greiner Bio‐One, cat# 96077440, Göttingen, Germany), covered with the UV‐transparent lid and the edges very safely sealed with parafilm.…”
Section: Methodsmentioning
confidence: 99%